Multiple inputs all-optical logic gates based on nanoring insulator-metal-insulator plasmonic waveguides - Hassan Falah Fakhruldeen; Tahreer Safa’a Mansour; Feryal Ibrahim Jabbar; Ahmed Alkhayyat (International Journal of Electrical and Computer Engineering (IJECE), 2022)
In this paper, we report new nanoscale plasmonic multiple inputs logic gates based on insulator-metal-insulator (IMI) nanoring waveguides. The proposed all-optical gates are numerically analyzed by the finite element method. NOT, AND, NAND, NOR, and EX-NOR all-optical logic gates were suitably designed and investigated based on the linear interface between the propagated waves through the waveguides. The operation wavelength was 1550 nm. The simulation results show that the optical transmission threshold of (0.26) which performs the operation of planned logic gates is accomplished. Moreover, simulation results show that our compact structure of all-optical logic gates may have potential applications in all-optical integrated networks.